Glucose Sensor Obtained by Recycling Copper from Li-Ion Batteries - Garcia, Eric M.; Taroco, Hosane A.; Melo, Julio O. F.; Rocha, Patrícia A.; Balestra, Roseli M.; Taroco, Cristiane G.; Gorgulho, Honória F. (Fine Chemical Engineering, 2025)
The sustainable transformation of electronic waste into high-value functional materials represents a crucial challenge in modern science. In this work, we report the fabrication of a non-enzymatic glucose sensor using copper directly recovered from the anode current collectors of spent lithium-ion batteries—without any additional chemical treatment or surface modification. The recycled copper was characterized by X-Ray Diffraction and applied as a working electrode in alkaline media, where its electrochemical behavior was investigated by cyclic and linear sweep voltammetry. The sensor exhibited excellent analytical performance, including a wide linear range up to 400 ppm glucose (R2 = 0.99), a low detection limit of 12.94 ppm (≈ 71.85 μmol·L-1), and a high specific sensitivity of 1,960 μA·mM-1·cm-2. Notably, common interferents such as fructose, uric acid, and ascorbic acid had negligible impact on the response, demonstrating strong selectivity. This study pioneers a cost-effective and environmentally friendly approach for electrochemical sensing, combining waste valorization with robust glucose detection, and advancing the circular economy through innovative material reuse.